SYNTHESIS AND CHARACTERIZATION OF NEW 2-OXAZOLINE MACROMONOMERS BY THE TERMINATOR METHOD - Carlos Rueda, Juan (2023)
New macromonomers of 2-oxazolines were synthetized from the cationic ring-opening polymerization of 2-ethyl-2-oxazoline or 2-methoxycarbonylethyl-2-oxazoline, obtaining the macromonomers M1 and M2, respectively. Polymerization was carried out in acetonitrile at 78°C and was initiated by methyl triflate and terminated by N-(4-vinyl-benzyl)-piperazine (“terminator” method).The macromonomers were characterized by proton nuclear magnetic resonance (NMR), infrared (FTIR) and ultraviolet/visible spectrometry (UV/Vis). It was determined by quantitative análisis of the 1H NMR spectra that the degrees of polymerization of the macromonomers M1 and M2 were 14 (molecular weight 1605 g/mol) and 12 units (2100 g/mol), respectively, agreeing these experimental values very well with the theoretical values (15 and 12). This fact was evidence that the polymerization was of “living” character and occurred without secondary reactions such as termination or chain transfer reactions.